Analysis of Competencies and Work Motivation as Determinants of Organizational Commitment and its Impact on Employee Performance at PT. Friends of Digital Printing - Budiarti, Rose; Suwandi, Yudi Wahyudin (TechTalent & Business Review, 2025)
This study aims to analyze the influence of competence and work motivation as determinants of organizational commitment and its impact on employee performance at PT. Friends of Digital Printing. The background of this research is based on the importance of continuous employee performance improvement through strengthening internal factors such as competence, work motivation, and organizational commitment that determine the effectiveness of human resources in the company. In the context of the competitive digital printing industry, employees' ability to adapt, work efficiently, and show loyalty to the organization is an important aspect in maintaining the company's sustainability and competitiveness. This research uses a quantitative approach with descriptive and verifiable methods. The research population is all employees of PT. Sahabat Digital Printing with a total of 67 respondents who were selected through saturated sampling techniques. Data collection was carried out through the distribution of questionnaires and field observations. Data analysis was carried out using path analysis. The results of the study show that the variables of competence and work motivation have a partial and simultaneous positive and significant influence on organizational commitment, and organizational commitment has a positive and significant influence. This research emphasizes the importance of human resource development strategies through technical and non-technical competency training, providing motivation oriented to individual needs, and strengthening organizational commitment to improve employee performance. Thus, the results of this research can be the basis for the management of PT. Sahabat Digital Printing in designing a more effective and sustainable HR development policy.